Fe3O4@ZIF-8: a magnetic nanocomposite for highly efficient UO22+ adsorption and selective UO22+/Ln3+ separation. Issue 30 (3rd March 2017) - Min, Xue; Yang, Weiting; Hui, Yuan-Feng; Gao, Chao-Ying; Dang, Song; Sun, Zhong-Ming
Abstract : Fe3 O4 @ZIF-8 nanoparticles with outstanding UO2 2+ adsorption capacity and selectivity for lanthanide ions could be simply separated by magnet from a solution containing lanthanide ions. Abstract : The magnetic nanocomposite Fe3 O4 @ZIF-8 was for the first time used as an excellent adsorbent for the fast adsorption and separation of UO2 2+ ions from aqueous solutions. This material exhibited an unprecedented adsorption capacity of 523.5 mg U per g and a remarkable selectivity towards UO2 2+ /Ln 3+ at pH = 3.